Legal Certainty Regarding the Material Value of Trademark Rights Certificates for UMKM Business Actors as Objects of Banking Guarantees - Febri Noor Hediati; Sulung Nugroho; Yennita Astarina; Dewi Atriani; Karenditha Virdara Suwarnie; Nandia Khalimatus Sa’diyah (Universitas Islam Lamongan, 2026)
This study aims to analyze the legal status of trademark certificates as banking collateral and to examine the legal certainty of their material value in credit financing under Government Regulation No. 24 of 2022 on the Creative Economy. This research adopts an empirical qualitative approach combined with normative legal analysis through statutory review, legal literature, and in-depth interviews with Micro, Small, and Medium Enterprises (MSMEs), financial institutions, and the Financial Services Authority. The data were analyzed descriptively to identify gaps between legal norms and practical implementation. The findings indicate that, legally, trademark certificates are recognized as intangible movable assets that may be used as fiduciary security; however, legal certainty regarding their material value remains insufficient. The main constraints include the absence of clear execution mechanisms, high valuation risk due to the subjective and volatile nature of trademark value, and the dependence of trademark value on the debtor’s business continuity. Furthermore, limited awareness among business actors and the lack of readiness of banking institutions to accept intangible assets as collateral widen the gap between regulation and practice. This study recommends harmonizing collateral law and intellectual property regulations, establishing standardized trademark valuation guidelines, and strengthening institutional capacity of financial institutions and business actors to support effective and sustainable intellectual property-based financing.